2018
DOI: 10.1080/07391102.2018.1505551
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in silico evaluation of fucosterol from Sargassum horridum as potential human acetylcholinesterase inhibitor

Abstract: The fucosterol has been reported numerous biological activities. In this study, the activity in vitro of the fucosterol from Sargassum horridum as potential human acetylcholinesterase inhibitor was evaluated. The structural identification was obtained by nuclear magnetic resonance (NMR) spectroscopy and based on experimental data, we combined docking and molecular dynamics simulations coupled to the Molecular-Mechanics-Generalized-Born-Surface-Area approach to evaluating the structural and energetic basis for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…However, AD pathology is accompanied by the cholinergic deficit, which could be compensated by the AChE inhibitor. Previous studies showing the inhibitory activity of fucosterol against AChE [12,28] and our molecular docking findings suggest that fucosterol could be a promising AChE inhibitor having clinical application in AD.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, AD pathology is accompanied by the cholinergic deficit, which could be compensated by the AChE inhibitor. Previous studies showing the inhibitory activity of fucosterol against AChE [12,28] and our molecular docking findings suggest that fucosterol could be a promising AChE inhibitor having clinical application in AD.…”
Section: Discussionsupporting
confidence: 66%
“…Evidence from the literatures supports its various biological activities, including antioxidant [6,7,8,9], anti-inflammatory [7,8,10,11,12,13], anticancer [14,15], antidiabetic [16], cholesterol homeostasis [17], cholesterol-lowering [18], antihyperlipidemic [19], hepatoprotective [6,20,21], immunostimulatory [22], antimicrobial [23], antiobesity [24,25], and antidepressant [26] potentials. Moreover, fucosterol exhibits inhibitory activity against acetyl- and butyryl-cholinesterase (AChE and BChE) [27,28] and β-secretase (an enzyme responsible for Aβ production, which is related to Alzheimer’s disease) [29]. Fucosterol also attenuated Aβ-induced neuronal death [27,30] and ameliorated cognitive impairment in the Aβ-induced neurotoxicity model of adult rats [30].…”
Section: Introductionmentioning
confidence: 99%
“…Another study also demonstrated anticholinesterase activity of fucosterol [ 85 ]. Enzyme kinetics and computational analysis indicated a non-competitive mode of acetylcholinesterase (AChE) inhibition of fucosterol [ 115 ].…”
Section: Neuropharmacological Potentials Of Marine Algae and Theirmentioning
confidence: 99%
“…In a recent study, fucosterol isolated from Sargassum horridum demonstrated potent inhibition against AChE activity [49]. Kinetic studies revealed that fucosterol showed competitive and non-competitive inhibition due to its high binding affinity to AChE compared to neostigmine.…”
Section: Therapeutic Role Of Some Macroalgae In the Management Of Admentioning
confidence: 99%